The Implementation of Learning Media in the Teaching Process of Productive Subjects in the Building Engineering Department at SMK Negeri 7 Semarang - Wijaya, Ahya ‘Alimah Rahmah Haque; Qudus, Nur; Sukamta, Sri (Universitas Negeri Semarang, 2024)
The use of learning media in vocational education, particularly in productive subjects at Vocational High Schools (SMK), plays a crucial role in enhancing students‘ understanding of technical concepts and preparing them for the workforce. This study aims to analyze the implementation of learning media in the teaching process of building engineering subjects at SMK Negeri 7 Semarang and to provide recommendations for developing effective and contextual learning media. A descriptive qualitative approach was employed, with participants including productive subject teachers, eleventh-grade students, and documents related to the Merdeka Curriculum. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles & Huberman. The findings indicate that visual-based, digital, and physical teaching aids significantly contribute to increasing student enthusiasm, focus, and comprehension of building construction materials. However, several challenges were identified, including limited infrastructure, low digital literacy among teachers and students, and dependency on licensed software. Based on these findings, it is recommended to develop collaborative, project- based, and locally contextualized learning media, enhance teacher capacity through educational technology training, and optimize digital platforms to support more inclusive and innovative learning experiences. Thus, the appropriate use of learning media can improve the quality of vocational education and strengthen students‘ readiness to meet job market demands in the field of building construction.